Integration of AI and FinTech in Digital Marketing to Improve Customer Experience - Mukhtar Galib; Syamsul Rijal (IECON: International Economics and Business Conference, 2024)
This study examines the impact of integrating artificial intelligence (AI) and financial technology (FinTech) in digital marketing to enhance customer experience. Through a literature-based approach, the study explores how AI and FinTech contribute to improving personalization, transaction ease, and security in digital marketing campaigns. The findings reveal that AI enables companies to analyze customer behavior in depth, providing more relevant recommendations and boosting customer engagement. Meanwhile, FinTech simplifies transaction processes and enhances security, which plays a crucial role in fostering customer satisfaction and loyalty. Together, AI and FinTech create a more personalized, secure, and efficient customer journey. However, the study notes some limitations, such as the restricted data coverage within the e-commerce and financial services sectors, which may not fully capture the potential of these technologies in other fields. Additionally, there is a potential for bias in the analysis due to the reliance on existing literature without experimental validation. Recommendations for future research include developing more adaptive AI technologies that can respond to dynamic customer preferences and expanding the scope of study to include sectors like healthcare and education. Overall, the integration of AI and FinTech in digital marketing holds significant promise for enhancing customer satisfaction and improving the effectiveness of marketing campaigns across various sectors.